Conflicts of interest and agent heterogeneity in buyer brokerage. (1st December 2022) - Kryzanowski, Lawrence; Wu, Yanting; Zhou, Tingyu
Abstract: This article investigates the incentives of agents working with buyers (buying agents) under the fixed percentage commission system and the implications on housing market outcomes. Our model shows that the absence of a binding contract creates a risk of losing clients for buying agents, which helps mitigate the conflict of interest between buying agents and their clients. Both the buying agent's prediction accuracy regarding their client's reservation prices and the level of tolerance given by the buyer to the buying agent affect the binding force. Results from simulations and empirical analyses using house transactions in Canada support our model predictions.